Zjednoczone Stronnictwo Ludowe w województwie zielonogórskim w latach 1956-1959. Konflikt o pozory władzy = The United People?s Party in Zielona Góra province between 1956-1959. Conflict about the semblance of power - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1959 supporters of greater independence of the peasant movement, such as Stanisław Obrębski and Zdzisław Szczęśniewski, took action intended to change the provincial authorities of the United People?s Party in Zielona Góra. Their efforts have proven to be ineffective, because the position of the president of these structures was kept by Stanisław Romanowski, the supporter of the close dependence of the United People?s Party on the Polish United Workers? Party.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia